Assessing soil quality indices based on soil organic carbon fractions in different long‐term wheat systems under semiarid conditions. (16th August 2019) - Duval, Matias E.; Martinez, Juan M.; Galantini, Juan A.
Abstract: The literature shows a great number of soil quality indices (SQI ) based on organic matter and its fractions. Our objectives were to determine the changes in soil organic carbon (SOC), carbon fractions and SQI in three production systems based on winter wheat ( Triticum aestivum L.). The three production systems involved wheat monoculture under conventional tillage and no‐tillage (WWCT and WWNT, respectively) and traditional management, wheat under conventional tillage and grazing of natural grasses, alternated one year each (WGCT ). In turn, each treatment was divided into N‐P‐fertilized (f) and non‐fertilized (nf). We analysed SOC, labile fractions and their ratios (SQI ) at 0–5, 5–10 and 10–20 cm soil depths. SOC was significantly higher in WWNT ‐f than in WWCT ‐f and WGCT ‐f at 0–5 and 0–20 cm range. Conversely, the lowest concentration was found in WWNT and WWCT in non‐fertilized plots. Particulate organic C (POC, 105–2, 000 μm) was significantly affected by tillage at 0–5 cm with the greatest concentrations found in WWNT (mean = 3.2 g kg −1 ) followed by WGCT and WWCT (mean = 2.0 g kg −1 ). Soils under CT showed the lowest lability index (LI) values, whereas the conversion to NT increased it (0.74–1.28). Carbon management index (CMI) increased significantly at the 0–20 cm seven years after NT establishment compared to WWCT . SQI such as LI, CMI and SOC/silt+clay were more sensitive for differentiating production systems, whereas C pool index and C/N were more sensitive for differentiating the fertilizer application effect. Considering improvement in SQI and carbon fractions as indicators of better soil quality, adoption of NT improved the soil quality in the semiarid rainfed conditions in the short term.